Standard levator aponeurosis / muscle resection with three point fixation versus two point fixation tucking for congenital ptosis with fair to good levator function - Heba Hamdy Ibrahim Mohamed; Dina Hossam Hassanien; Rania Assem Elessawy; Sameh Hassan Abdelbaky (Cairo : Heba Hamdy Ibrahim Mohamed, 2017)
Objective: To evaluate the surgical effect of standard three point fixation levator resection and a two point fixation levator tucking for congenital ptosis. Patients and methods: A prospective, randomized, comparative and interventional study that included 40 children, who presented to the ophthalmology clinic at Cairo university specialized Pediatric Hospital with congenital ptosis. They were randomized to either levator resection or tucking. Outcome was compared in terms of eyelid height and eyelid contour. Data was compared using the paired and unpaired test. Results:Successful outcomes of the two techniques regarding MRD 1 within 3-5 mm were similar in both groups at the end of follow up (three months) as met by 18 (85.7%) eyelids of 21 eyelids in each group. Regarding {u2264}1 mm difference in eyelid height was met by 14 (66.67%) eyelids of 21 eyelids in group A and in group B met by 16(76.2%) eyelids of 21 eyelids. Good eyelid contour was met in group A by 17(80.95%) eyelids of 21 eyelids, while in group B it was met by 16 (76.2%) eyelids of 21 eyelids. Conclusion: Levator resection and levator tucking are both effective cosmetically and functionally for congenital ptosis repair, however levator tucking has many advantages over levator resection
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Ophthalmology
Issued also as CD
Keywords: Congenital ptosis; Levator resection; Levator tucking